PENGARUH JARAK TANAM DAN PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (ZEA MAYS SACCHARATA STURT) - Resdiar, Amda (Universitas Teuku Umar, 2017)
This study aims to determine the effect of plant spacing and proper organic fertilizer on the growth and production of sweet corn and the interaction between the two factors. The research method used in this research is Randomized Block Design (RBD) 3 x 3 factorial pattern with three replications. Factors studied include plant spacing and dosage of organic fertilizer. Factors studied include plant spacing with 3 levels ie 50 x 20 cm (J1), 70 x 20 cm (J2), and 90 x 20 cm (J3). The dosage factor of organic fertilizer consisting of 3 levels is 10 tons ha-1 (P1), 20 tons ha-1 (P2) and 30 tons ha-1 (P3). The results showed that plant spacing had significant effect on plant height 15, 30 and 45 DAP, cob weight without weight and production of ha-1 but not significant effect on leaf age 15, 30 and 45 DAP, length of cob and diameter of cob. The results showed that organic fertilizer had very significant effect on plant height aged 30 and 45 DAP, cob weight without weight and production of ha-1 and significant effect on plant height of 15 DAP but no significant effect on the number of leaves aged 15, 30 and 45 DAP , length of cob and diameter of cob without weight. There was no interaction between plant spacing and organic fertilizer on all growth variables and sweet corn yields observed. Keywords: plant spacing, organic fertilizer, sweet corn